Fit-in ice condenser: Microwave Assisted Organic Synthesis- Domestic Approach - Mohamad, Sabah Ahmed Adam; Garelnabi, Elrashied A. E. (Khartoum Journal of Pharmaceutical Sciences, 2021)
The main reason that organic research is lacking in developing countries like Sudan is the time- consuming nature of this type of research. Microwave induced organic synthesis overcomes that obstacle. Due to the a lack of special microwave reactors, special fit-in ice condenser for use with domestic microwave oven (DMO) was developed in this study. The esterification reaction (Diclofenac, Indomethacin, Ibuprofen methyl esters, and acetylsalicylic acid) was selected for assessment of the utility of the device.Time was reduced from the hours scale into minutes, accompanied by a reasonable increase in % yield. DMO synthesis of Diclofenac, Indomethacin, Ibuprofen methyl esters and acetylsalicylic acid was carried in 4, 8, 7.5 , and 2 min respectively. Compared with 6 h to overnight wait by the conventional method.